Fluctuations in the numbers of wildfowl on an equatorial hippo wallow - Eltringham, S K (Wildfowl, 1973)
Counts of wildfowl were made on an equatorial hippo wallow in Uganda from February 1968 to June 1972 at an average rate of six counts each month. Thirteen species of wildfowl were recorded including six palaearctic migrants. The Egyptian Goose Alopochen aegyptiacus was the only species present on all occasions but its numbers varied considerably. No obvious pattern was apparent. Other Ethiopian species appeared erratically. Up to 700 Garganey Anas querquedula and 250 Northern Pintail Anas acuta occurred during the palaearctic winter. The pattern of movements differed markedly each year and it is suggested that many of these were passage migrants resting on their way to or from wintering areas further south.